The Australian Royal Commission into the Aged Care Industry 2019 - W. Harvey, Peter (Journal of Aging Research And Healthcare, 2019)
In the light of various complaints about the quality of care provided by and operation of aged care facilities across Australia, the Commonwealth Government has announced a Royal Commission into the activities of the sector. As the proportion of Australians over 65 continues to grow with the ageing of the ‘Baby Boomer’ generation, more Australians are seeking secure aged care arrangements to meet their increasingly complex living and healthcare needs. We hear much comment today about the concept of healthy ageing and the importance of older people staying connected to and active in their communities. Not only does this ongoing connectivity support better lifestyles and health status, it provides an avenue for older people to contribute to the support of others once their more formal working lives are concluded. Unfortunately, the gap between the rhetoric and the reality of ageing in Australia is strained and it appears that much about the operations of the aged care sector today is less than satisfactory. While some well-funded retirees can afford comfortable and fulfilling living arrangements, many others are left in less ideal circumstances. With aged care organisations currently building the next generation of ‘hotel’ style living arrangements for cashed up self-funded retirees, others are being left behind financially and in terms of the quality of their care. At the same time, maltreatment and abuse of residents is coming to light, as in the ‘Oakden Nursing Home’ situation in South Australia, for example. Consequently, the Federal Government has now launched a formal inquiry into the activities of organisations running aged care facilities in Australia. The inquiry is designed to assess the operation of this industry with a focus on the economics of aged care centres, the quality of care, the food and recreational activities provided and the challenge of staffing these facilities to keep residents safe and well as they age in dignity.
Keywords: Aged Care; Royal Commission; Quality of Care; Healthy Ageing; Staffing Levels; Australia